PROBLEMATIKA PELAKSANAAN PEMILIHAN KEPALA DESA SERENTAK PASCA UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA (Studi Di Kabupaten Tegal) - Nuriman, Nuriman (Jurnal Idea Hukum, 2020)
Democracy stands on the principle of equality, namely that every citizen has equal rights and positions within the government, in which case the people are given the power to participate in determining the government that the authority of the ruler comes from the legitimacy of the people. To find out and analyze the problematic that occurred in the Implementation of Village Head Selection Simultaneously After Law No. 6 of 2014 about villages in Tegal Regency and to provide solutions so that similar problems do not occur again. The approach method used in this study is the normative Juridical method. The data analysis used is qualitative analysis. In the case of simultaneous village head selection in Tegal Regency year 2017 due to the symmetrical coblosan of many valid ballots declared invalid by the Village Head Selection Committee so that many parties do not accept the results of the election of the Village Head simultaneously. In addition, invalid ballots are much more than the highest vote-get-off of village chiefs.